Analisis Pengaruh Pertumbuhan Ekonomi, Jumlah Pengangguran Dan Indeks Pembangunan Manusia Serta Inflasi Terhadap Tingkat Kemiskinan Di Kabupaten Malinau (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2018)
The purpose of this research was to analyze the effect of economic growth, unemployment, Human Development Index (HDI), and inflation on poverty rate in Malinau Regency.The secondary data analysis applying multiple linear regression to analyze the effect of four independent variables: economic growth (X1), unemployment (X2), Human Development Index (X3) and inflation (X4) on poverty rate (Y) as the dependent variable in Malinau Regency, North Kalimantan Province from 2004 to 2013.The result of F test analysis simultaneously showed that there was a significant effect of the independent varibles on the dependent variable. The regression coefficient of F-value was15.409 with signficance level 0.005 ( < 0.05). This indicated that the model analysis was appropriately used in this research. Furthermore, T test for the partial regression found thateconomic growth (X1) had a positively insignificant effect on poverty rate (Y). Meanwhile, the other two variables: unemployment (X2) and inflation (X4) showed a negatively insignificant effect on poverty rate (Y). Last but not least, Human Development Index (X3) had a negatively significant effect on poverty rate (Y).In conclusion, Human Development Index (HDI) is the most dominant variable affecting poverty rate in Malinau Regency, North Kalimantan Province. The Standardized Coefficients Beta of HDI is the greatest among the other variables.